Preview From Notesale - Co.uk Page 1 of 15: Advanced Calculus - Integration
Preview From Notesale - Co.uk Page 1 of 15: Advanced Calculus - Integration
Preview From Notesale - Co.uk Page 1 of 15: Advanced Calculus - Integration
George Beresford
November 28, 2013
k
u
.
.co
e
l
a
s
e
t
o
N
5
m
1
o
r
f
f
o
w
1
e
i
e
v
e
r
Pag
P
1.5.1
Example 5
Rx
Rx
We can show that a (t + 1) dt = 21 (x2 a2 ) + (x a). This means that A(x) = a (t + 1) dt =
1
(x2 a2 ) + (x a). Differentiating A(x) we get,
2
1
A0 (x) = (2)(x) + 1 = x + 1 = f (x)
2
1.5.2
Example 6
Let f (x) = 3x2 . We observe that if F (x) = x3 then F 0 (x) = 3x2 = f (x). Part (2) of the fundemental
theorem of Calculus states,
Z b
3x2 dx = F (b) F (a) = b3 a3
a
1.6
If f is a continuous function and F is any function such that F 0 (x) = f (x), then F is said to be an
antiderivative of f . F is also known as the primitive integral or the indefinite integral.
1.6.1
Part 1
A(x + h) A(x)
h0
h
A0 (x) = lim
Z
x+h
Z
f (t) dt
A(x + h) A(x) =
Z
f (t) dt +
f (t) dt =
k
u
.
.co
x+h
e
l
a
s
e
t
o
N
5
m
1
o
r
f
f
o
w
8
e
i
e
v
e
r
Pag
P
a
f (t) dt
f (t) dt
x+h
f (t) dt
A0 (x) = lim
Part 2
Rb
Rx
If F 0 (x) = f (x) then, a f (x) dx = F (b) F (a). From part (1), A(x) = a f (t) dt satisfies A0 (x) = f (x).
Introducing the equation G(x) = F (x)A(x) = G0 (x) = F 0 (x)A0 (x) = G(x) = f (x)f (x) = 0.
So G is a constant, G(x) = c. So F (x) = A(x) + G(x) = F (x) = A(x) + c. So,
Z x
F (x) =
f (t) dt + c
a
as
Ra